Fate of the Uninsured Ankle Fracture: Significant Delays in Treatment Result in an Increased Risk of Surgical Site Infection. Issue 3 (March 2021) - Zelle, Boris A.; Johnson, Taylor R.; Ryan, James C.; Martin, Case W.; Cabot, John H.; Griffin, Leah P.; Bullock, Travis S.; Ahmad, Farhan; Brady, Christina I.; Shah, Kush
Abstract : Objective: To examine the impact of insurance status on access to orthopaedic care and incidence of surgical site complications in patients with closed unstable ankle fractures. Design: Retrospective chart review. Setting: Certified Level-1 urban trauma center and county facility. Participants: Four hundred eighty-nine patients with closed unstable ankle fractures undergoing open reduction and internal fixation between 2014 and 2016. Intervention: Open reduction and internal fixation of unstable ankle fracture. Main Outcome Measures: Time from injury to presentation, time from injury to surgery, rate of surgical site infections, and loss to follow-up. Results: A total of 489 patients (70.5% uninsured vs. 29.5% insured) were enrolled. Uninsured patients were more likely to be present to an outside hospital first ( P = 0.004). Time from injury to presentation at our hospital was significantly longer in uninsured patients (4.5 ± 7.6 days vs. 2.3 ± 5.5 days, P < 0.001). Time from injury to surgery was significantly longer in uninsured patient (9.4 ± 8.5 days vs. 7.3 ± 9.1 days, P < 0.001). Uninsured patients were more likely to be lost to postoperative follow-up care ( P = 0.002). A logistic regression analysis demonstrated that delayed surgical timing was directly associated with an increased risk of postoperative surgical site infection ( P = 0.002). Conclusions: Uninsured patients with ankle fractures requiring surgery experience significant barriers regarding access to health care. Delay of surgical management significantly increases the risk of surgical site infections in closed unstable ankle fractures. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.